A taxonomic account on the phytoplankton of a pond receiving textile industrial effluents. II. Euglenophyceae and Bacillariophyceae - Begum, Z.N. Tahmida (Bangladesh Journal of Plant Taxonomy, 2009)
A total of 97 phytoplanktonic algal taxa belonging to 17 genera under two classes (Euglenophyceae and Bacillariophyceae) have been recorded from a pond receiving effluents from two textile industries at Demra, Dhaka district. Five diatom species, namely Navicula cryptocephala Kütz., N. decussis Oestrup, N. rhynchocephala Kütz., N. viridula Kütz. and Nitzschia intermedia Hantzsch are new records for Bangladesh. Keywords: Industrial effluents; Phytoplankton; Taxonomy; Euglenophyceae; Bacillariophyceae. DOI: 10.3329/bjpt.v16i1.2742 Bangladesh J. Plant Taxon. 16(1): 9-19, 2009 (June)